Političnost ob stoletnici Bertolta Brechta - Suvin, Darko (Primerjalna književnost, 2006)
Centennial Politics: On Jameson on Brecht on Method. The paper reflects on Fredric Jameson's book Brecht and Method (London and New York: Verso, 1998), starting with Jameson's assertion that there existed a Brechtian "stance" or "method", which combined doctrine, narrative and style. Attention is focused on Brecht's storytelling depicted as a kind of cognition.
Keywords: Brecht, Bertolt, 1898-1956; književnost; literature; ideologija; German-language literature; nemška književnost; 20.st.; politična drama; politično gledališče